2007
DOI: 10.1108/10662240710737004
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing online music purchase intention in Taiwan

Abstract: Purpose -The purpose of this paper is to provide an explanation of factors influencing online music purchase intention of Taiwanese early adopter of online music, which can help the online music practitioners of Taiwan to develop better market strategies. Design/methodology/approach -An empirical survey was used to test the hypotheses. Data were collected from a total of 302 online Taiwanese early adopters of online music. A structural equation modeling (SEM) is proposed to assess the relationships of the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(108 citation statements)
references
References 36 publications
7
81
1
19
Order By: Relevance
“…Similar with Ching and Hsi (2007); Mahmud et al (2008); Eggert and Ulaga (2002), which indicate that perceived value have positive association with purchase decision, our results also indicate that value is another factor customers will concern about when they want to purchase cars. This is because same positive questions have been used in our questionnaire to measure perceived value in our questionnaire as others researchers done.…”
Section: Resultssupporting
confidence: 75%
“…Similar with Ching and Hsi (2007); Mahmud et al (2008); Eggert and Ulaga (2002), which indicate that perceived value have positive association with purchase decision, our results also indicate that value is another factor customers will concern about when they want to purchase cars. This is because same positive questions have been used in our questionnaire to measure perceived value in our questionnaire as others researchers done.…”
Section: Resultssupporting
confidence: 75%
“…Chu & Lu (2007) found that the perceived effectiveness of a product has a significant influence on the consumer's purchase intention. Similarly, Lin & Tsai (2006) found that consumers might decide to purchase a product/service when they think the product is effective.…”
Section: Purchase Intentionsmentioning
confidence: 99%
“…We used online questionnaire because of the ease of using them to target respondents who have used MSNAs on mobile devices (Chu and Lu, 2007). We uploaded the questionnaire to the website of an online marketing survey company in Taiwan and made them available for 1 month (December 12, 2012 until January 12, 2013).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%